1986
DOI: 10.3109/00365548609032342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Beta-lactamase Activity and Microbial Interference in Treatment Failures of Acute Streptococcal Tonsillitis

Abstract: Out of 169 patients with streptococcal tonsillitis treated with phenoxymethylpenicillin, 13 (8%) developed a new clinical infection with the same streptococcal strain within 2 weeks of completing the therapy (clinical treatment failure) and 24 (14%) were clinically healthy but harboured the same streptococcal strain after treatment (bacterial treatment failure). Patients with clinical treatment failure showed beta-lactamase activity in their saliva pellet significantly more often than patients with bacterial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 24 publications
2
35
0
1
Order By: Relevance
“…Mechanisms that may explain penicillin treatment failure have been explored extensively. These mechanisms include elimination of commensal organisms (6,13,28), viral copathogenicity (16), internalization of GAS in epithelial cells (21,23), and bacterial copathogenicity (6,7,28,34). To date, none of these mechanisms, either individually or in combination, completely explains the occurrence of penicillin treatment failure observed in clinical practice.…”
mentioning
confidence: 99%
“…Mechanisms that may explain penicillin treatment failure have been explored extensively. These mechanisms include elimination of commensal organisms (6,13,28), viral copathogenicity (16), internalization of GAS in epithelial cells (21,23), and bacterial copathogenicity (6,7,28,34). To date, none of these mechanisms, either individually or in combination, completely explains the occurrence of penicillin treatment failure observed in clinical practice.…”
mentioning
confidence: 99%
“…This led to the hypothesis that bacteriocin production may result from a selective pressure exerted by GABHS and also that these substances might actually inhibit colonization of the upper respiratory tract and/or aid in the eradication of GABHS. Roos and col-leagues (20) demonstrated that both production of ,B-lactamase by the normal oropharyngeal flora and the lack of colonization of the pharynx with inhibiting AHS correlated with the failure of penicillin to cure GABHS tonsillitis. Although only a single strain of each organism was used in the present study, the isolates that we used represent typical isolates of each bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of aerobic and anaerobic BLPB in over threequarters of patients with recurrent GABHS tonsillitis (1,7,13), the ability to measure ␤-lactamase activity in the tonsillar core (2), and the response of patients with recurrent GABHS tonsillitis to antimicrobials effective against BLPB (1,5,7,13) support this explanation.…”
mentioning
confidence: 92%
“…One explanation of this phenomenon is that ␤-lactamase-producing bacteria (BLPB) protect GABHS by inactivating penicillin (1). Another explanation is that the preservation of alpha-hemolytic streptococci (AHS) that possess interfering capabilities against GABHS contribute to the eradication of this organism (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation